KONSISTENSI PENGADILAN NEGERI DALAM MEMUTUSKAN WANPRESTASI DALAM PERJANJIAN KERJA (PUTUSAN KASASI NOMOR 1706/PDT/2013 DAN PUTUSAN KASASI NOMOR 322/PDT.G/2015/PN.JKT.TIM) - Yusmita Sari; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2018)
A working relationship between the employers with workers or labourers often inconsistent like what to expected, so often cause of disputes. The purpose of this journal is to know how the Consistency of the District Court in Deciding Default in the Employment Agreement based on concideration and decisions from judge of verdict of appeal number 1706/PDT/2013 and verdict of appeal number 322/Pdt.G/2015/PN.Jkt.Tim. This study is a normative legal research methods supported by some interview is expected to help answer the problem of this research. the result of this study are : first the service bond agreement can not be equalized with the employment agreement. because they both agreements have different elements. the service bond agreement is an ordinary civil agreements, not regulated by law no 13 of 2003 about employment.second, Industrial relation court is a special court in general court. They both have a difference of authority. Industrial relations courts are authorized to adjudicate disputes from employment agreements while state courts are authorized to adjudicate disputes from service bond agreements. Appellate court as the highest court of the country must prioritize justice and legal certainty and must explicitly decide on the actual decision.